Legal Responsibility of Debitur to Creditors For Acts Against the Law in Credit Agreements : (Study of Decision Number 1060/Pdt.G/2023/PN Mdn) - Wilda Hilda Riska Laia; Roida Nababan; Besty Habeahan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Agreement is one of the most important sources of engagement in civil law. In practice, agreements become the legal basis for parties to regulate mutual rights and obligations. As in credit agreements where credit agreements are one of the most common forms of agreements in banking practices and financing activities in Indonesia. This agreement becomes the legal basis for the relationship between creditors and debtors in the context of providing loan facilities. This article discusses the juridical aspects of credit agreements, starting from the elements of a valid agreement, the principles that underlie it, to the legal consequences that arise in the event of default or unlawful acts by one of the parties. The research was conducted using a normative juridical method that focuses on analyzing laws and regulations, especially the Civil Code and the Banking Law. The results of the study show that credit agreements are not only civilly binding, but also contain potential criminal law consequences in the event of misuse. Therefore, it is important for the parties to understand the contents and legal consequences of the credit agreement thoroughly.